2016
DOI: 10.1099/ijsem.0.001501
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplasma classification and phylogeny based on in silico and in vitro RFLP analysis of cpn60 universal target sequences

Abstract: Phytoplasmas are unculturable, phytopathogenic bacteria that cause economic losses worldwide. As unculturable micro-organisms, phytoplasma taxonomy has been based on the use of the 16S rRNA-encoding gene to establish 16Sr groups and subgroups based on the restriction fragment length polymorphism (RFLP) pattern resulting from the digestion of amplicon (in vitro) or sequence (in silico) with seventeen restriction enzymes. Problems such as heterogeneity of the ribosomal operon and the inability to differentiate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…2b). RFLP analysis of the cpn60 UT sequence (Pérez-López et al 2016b) showed that phytoplasma strain GWL-Ver was a member of the previously described (Pérez-López et al 2016b) cpn60 UT I-IIIB subgroup (not shown).…”
mentioning
confidence: 69%
“…2b). RFLP analysis of the cpn60 UT sequence (Pérez-López et al 2016b) showed that phytoplasma strain GWL-Ver was a member of the previously described (Pérez-López et al 2016b) cpn60 UT I-IIIB subgroup (not shown).…”
mentioning
confidence: 69%
“…This created misleading genetic similarities among unrelated taxa at the 16S rRNA gene. In general, these single-locus similarities often cannot fully reflect whole-genome relationships due to the horizontal transfer of genes, especially between bacteria that share the same ecological niche (for a sampling of recent discussions on the issues surrounding the use of 16S rRNA sequencing and the necessity for analysis of multiple loci, see references [29][30][31][32][33][34][35][36][37][38].…”
Section: Resultsmentioning
confidence: 99%
“…Although 16S rRNA sequencing is a powerful tool for assigning taxonomy of many bacteria, there are several pitfalls when using single-gene analyses to distinguish between bacterial strains (29)(30)(31)(32)(33)(34)(35)(36)(37)(38). The presence of both B. laterosporus and P. larvae in beehives, along with their taxonomic relatedness in the Paenibacillaceae family, may facilitate horizontal gene transfer, complicating the identification of bacterial isolates from beehives.…”
Section: Discussionmentioning
confidence: 99%
“…The restriction digestion pattern of one of these genes corresponded to 16SrI-B ( F = 1.00) using the i PhyClassifier ( 10 ), while the other copy corresponded to 16SrI-A ( F = 0.97). The single-copy phytoplasma taxonomic marker cpn60 ( 11 ) typed as I-IB ( F = 1.00) using random fragment length polymorphism (RFLP) analysis ( 12 ). Other taxonomic markers, including secY , secA , nusA, and rp , were also found in a single copy in the genome sequence.…”
Section: Announcementmentioning
confidence: 99%